Anxiety and Sensory Over-Responsivity in Toddlers with Autism Spectrum Disorders: Bidirectional Effects Across Time - Green, Shulamite A. (2012)
This report focuses on the emergence of and bidirectional effects between anxiety and sensory over-responsivity (SOR) in toddlers with autism spectrum disorders (ASD). Participants were 149 toddlers with ASD and their mothers, assessed at 2 annual time points. A cross-lag analysis showed that anxiety symptoms increased over time while SOR remained relatively stable. SOR positively predicted changes in anxiety over and above child age, autism symptom severity, NVDQ, and maternal anxiety, but anxiety did not predict changes in SOR. Results suggest that SOR emerges earlier than anxiety, and predicts later development of anxiety.